Assisting Children in Facing Digital Risks: The Role of Values and Communication - Hendriani, Wiwin; Fitrianetha, A’ida Fayza; Najah, Naya Shafina; Wulandari, Primatia Yogi; Cahyono, Rudi (Universitas Ahmad Dahlan, 2025)
The rapid development of the digital world presents numerous potential risks, particularly for children. Compared to other age groups, children are at a heightened risk of exposure to inappropriate content, cyberbullying, and privacy violations due to their limited ability to protect themselves. Parental guidance plays a crucial role in helping children navigate these digital dangers. This study aims to explore the internal factors of parents and their role in supporting children in managing digital risks. Using a qualitative approach and a case study methodology, the study involved four parents of children aged 7 to 12 years who were actively engaged in managing digital risks. Data collection consisted of online surveys, followed by interviews and self-report documents, all of which were analyzed using thematic analysis. The findings highlight that internal factors such as parental values and communication significantly influence how effectively parents can support their children in addressing digital risks. Based on these results, it is recommended that future interventions and support programs for parents focus on strengthening communication skills and aligning family values to better equip parents in guiding their children through digital challenges.